(untitled) (Journal of Plant Disease Sciences, 2021)
Aschersonia aleyrodis (Webber) potential biological control agents against Aleyrodidae and Coccidae family insect pest. Different commonly available food grains as solid substrate were evaluated for mass scale production of fungus A. aleyrodis under laboratory condition. Among all the grains/substrates, sorghum grains resulted in significantly highest spore production (3.43 x 107 conidia/g) with shorter period (16.67 days) followed by Wheat (3.30 x 107 conidia/g), Sunhemp (3.27 x 107 conidia/gm) and Maize (3.17 x 107 conidia/g). Rice, Barley, Fox millet and Pigeon pea were found least preferred grains for sporulation of A. aleyrodis. The lower conidial production was noticed in Groundnut kernels (1.02 x 107 conidia/g).